Pattern of Lue house: Orientation, Spatial Organization, and Hierarchy of Space, the Case in Manhong, Mengmanzhen, Xishuangbanna, China - Muenkhamwang, Thanick; Kirdsiri, Kreangkrai (Journal of Architectural/Planning Research and Studies (JARS), 2020)
This article focuses on the study of Tai Lue houses pattern in Manhong Village, Mengmanzhen, Xishuangbanna of China, one of the important villages in Mengmanzhen. By analyzing all 3 issues, including house orientation, spatial organization, and hierarchy of space. And to find for factors that affect the preservation and changing of house patterns. The author uses methods of study by reviewing secondary data sources and collecting data in the field with the methods: observation, semi-structured interviews, photography, and architectural measuring surveying. Selected houses with methods: purposive sampling, choosed the old houses where located in the center of the village, has 14 different forms, 90 out of a total. Then setting code to the houses, information management, and draw the architectural drawing to use in the analysis as objectives. With the aim of being a pilot study area, can be used as an example in the study of Tai Lue vernacular architecture in other continuous areas or taken to compare with the ethnic group who speak Thai language or other ethnic groups.